The Role Of Customer Financial Statements In Providing Credit At Bank Bengkulu Putri Hijau Sub-Branch Office - Adhitya Al-Fikri; Sulisti Afriani; Ramadhan Subhi (UNIVED Press, 2025)
The purpose of this study is 1) To identify and analyze the role of financial reports in the credit granting process at Bank Bengkulu KCP Putri Hijau, 2) To determine the financial report elements that are of primary concern in credit evaluation at Bank Bengkulu KCP Putri Hijau, 3) To understand and evaluate the relationship between financial reports and credit risk at Bank Bengkulu KCP Putri Hijau. The analytical method used in this study is a qualitative descriptive method using the interactive model of Miles and Huberman.The research findings indicate that financial reports play a key role in credit granting by Bank Bengkulu KCP Putri Hijau. Financial reports provide information about the financial health of customers, portfolio performance, and the level of risk faced, which are used to determine credit policies, resource allocation, and risk management to ensure the bank remains stable and competitive. Some key financial report elements in credit evaluation at Bank Bengkulu KCP Putri Hijau are the items in the income statement such as net operating income and net profit. As for the balance sheet, the focus is on total current assets and total assets. The relationship between financial reports and credit risk at Bank Bengkulu KCP Putri Hijau is analyzed through financial ratios such as Debt Service Coverage Ratio (DSCR), Current Ratio, Net Profit Margin (NPM), and Return on Assets (ROA). These ratios help assess the company's ability to service debt, thereby minimizing credit risk or defaults before credit approval is granted.